Maturity-Onset Diabetes of the Young (MODY) caused by a novel nonsense mutation E41X in the HNF-1α gene - Buchbinder, Susanne; Zorn, Markus; Bierhaus, A.; Nawroth, Peter Paul; Müller-Hennessen, Matthias; Schilling, Tobias (Experimental and clinical endocrinology & diabetes, 2011)
The most common cause of Maturity-Onset Diabetes of the Young (MODY) are mutations in the Hepatic Nuclear Factor 1α (HNF-1α) gene, resulting in MODY3. In a family afflicted with diabetes, a novel nonsense mutation in HNF-1α, E41X, causing a termination codon behind the dimerization domain, was found. The penetrance in individuals older than 25 years was 81.8%. The age at manifestation of diabetes ranged from 18 to 63 years, only 2 out of 10 diabetic individuals developed the disease at ages younger than 25 years. Although diabetes duration lasted up to 35 years in this family, only one family member suffered from diabetic complications. Additional polymorphisms in HNF-1α, I27L and S487N, were found in this pedigree. Despite its biological inactivity, S487N polymorphism led in combination with E41X to a significant earlier manifestation of diabetes, whereas I27L polymorphism or increased Body Mass Index (BMI) did not. In spite of the severe gene defect, which truncates the protein behind the dimerization domain, the phenotype of E41X was relatively benign without frequent diabetic complications.
05. August 2010 (online)
Gesehen am 24.06.2022